1981
DOI: 10.4319/lo.1981.26.6.1111
|View full text |Cite
|
Sign up to set email alerts
|

Oceanography of the eastern Bering Sea ice‐edge zone in spring1

Abstract: The ice-edge region of the southeast Bering Sea was studied in terms of the hydrographic regime, phytoplankton biomass, and primary productivity during the springs of 1975 through 1977. The results showed that a phytoplankton bloom occurs at the ice edge just as the spring ice-decay period begins, and that this accounts for a significant proportion of the annual carbon input over the shallow shelf. The bloom is intensified in time and space by the influence of the ice edge on the physical structure of the wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(85 citation statements)
references
References 10 publications
6
79
0
Order By: Relevance
“…Unfortunately, the salinity stratification is difficult to infer using satellite or reanalysis data. However, Alexander and Niebauer (1981) showed that the development of both salinity and thermal stratification induces water column stability, which generally triggers the ice-edge phytoplankton bloom in the Bering Sea. Thus, OHC was used as a proxy of the development of the surface mixed layer.…”
Section: Influence Of Tsr On Phytoplankton Size Composition During MImentioning
confidence: 99%
“…Unfortunately, the salinity stratification is difficult to infer using satellite or reanalysis data. However, Alexander and Niebauer (1981) showed that the development of both salinity and thermal stratification induces water column stability, which generally triggers the ice-edge phytoplankton bloom in the Bering Sea. Thus, OHC was used as a proxy of the development of the surface mixed layer.…”
Section: Influence Of Tsr On Phytoplankton Size Composition During MImentioning
confidence: 99%
“…Ice remains there longer there than in the southeastern Bering Sea, and shows less interannual variation . Thus, it might be expected that most phytoplankton production there would be associated with the melting of the sea ice and would occur in cold water as described by Alexander and Niebauer (1981) and Niebauer, Alexander & Henrichs, 1990, 1995. These conditions might be expected to result in slower growth and a lesser production of zooplankton, and thus a bottom-up limitation of fish recruitment compared to farther south on the shelf.…”
Section: The Oscillating Control Hypothesismentioning
confidence: 99%
“…Studies of springtime primary production in the mid1970s emphasized the importance of ice-associated blooms that occurred in cold water (-1°C) (e.g. Alexander & Niebauer, 1981;Niebauer, Alexander & Henrichs, 1990), whereas those working in the late 1970s and early 1980s emphasized the importance of open water blooms that occurred in comparably warm water (2°-5°C) (e.g. Sambroto et al, 1986;Walsh & McRoy, 1986).…”
Section: Biological Responses To Changes In the Marine Climatementioning
confidence: 99%
“…These interactions, which include water-column stratification from sea-ice melt (Alexander and Niebauer, 1981), eddies, and wind-driven vertical mixing of nutrients into surface waters, provide the components necessary for high primary productivity.…”
Section: Introductionmentioning
confidence: 99%